2015
DOI: 10.1097/mpa.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Toll-Like Receptor Polymorphisms in Acute Pancreatitis Occurrence and Severity

Abstract: Our article points to genetic polymorphisms in TLR3 and TLR6 as having a plausible role in the occurrence of severe AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 37 publications
1
12
0
1
Order By: Relevance
“…previous study indicated that serum amylase is always high in AP (30). Matas-Cobos reported increased serum amylase levels in AP, which was consistent with the present study (31). Therefore, the results indicated that DUSP1 gene silencing upregulated the expression of proinflammatory cytokines, HMGB1, S100A12 and amylase.…”
Section: Discussionsupporting
confidence: 92%
“…previous study indicated that serum amylase is always high in AP (30). Matas-Cobos reported increased serum amylase levels in AP, which was consistent with the present study (31). Therefore, the results indicated that DUSP1 gene silencing upregulated the expression of proinflammatory cytokines, HMGB1, S100A12 and amylase.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that many lifestyle choices and environmental factors such as excessive drinking, pancreatic duct strictures, viral or bacterial infection, hyperlipidemia, metabolic disorders, and infections are associated with disease susceptibility (Álvarez et al, 2015;Greer et al, 2015;Pohl and Uc, 2015;Talukdar and Vege, 2015;Tun-Abraham et al, 2015). Recent studies have reported that genetic factors play an important role in the pathogenesis of acute pancreatitis, such as interleukin-1β (IL-1β), IL-8, IL-10, heme oxygenase-1 gene, Toll-like receptor gene, tumor necrosis factor alpha gene, and heat-shock protein 70-2 gene (Özhan et al, 2010;Bishehsari et al, 2012;Srivastava et al, 2012;Gulla et al, 2014;Li et al, 2015;Matas-Cobos et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors observed a significant association of the synonymous variant c.180C > T (p.G60=) with CP [7, 16, 18, 19]. In the Indian studies, the variant c.180C > T (p.G60=) was found in 23–29% of the subject population.…”
Section: Discussionmentioning
confidence: 99%